Evaluation of the Manchester Triage System quality indicator: service time - Ana Paula Santos de Jesus; Ruth Ester Assayag Batista; Cassia Regina Vancini Campanharo; Maria Carolina Barbosa Teixeira Lopes; Meiry Fernanda Pinto Okuno (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: to verify the conformity of the time interval between the end of the risk classification and the beginning of medical care with that recommended by the Manchester protocol and to relate the times of care and the risk categories with the outcome. Method: Cross-sectional, retrospective, and analytical study. The t test, the analysis of variance and the generalized linear model were used. Results: The average time for medical care in the red and orange categories was 3 and 39.5 minutes, respectively. Death outcome was associated with the red category, with an average time to start the classification of 5.5 minutes and an average length of stay of 2.3 hours. Conclusion: The waiting time for medical care in the high priority categories was longer than recommended, which suggests the need to continuously monitor the system. Shorter waiting times for classification and permanence were related to the red category and the outcome of death.